Crucial Role of Oxygen Vacancies in Scintillation and Optical Properties of Undoped and Al-Doped β-Ga2O3 Single Crystals - Ruifeng Tian; Mingyan Pan; Qinglin Sai; Lu Zhang; Hongji Qi; Hany Fathy Mohamed (Crystals, 2022)
In this paper, the effects of oxygen vacancy and gallium vacancy on the optical and scintillation properties of undoped β-Ga2O3 crystal and 2.5 mol % Al doped gallium oxide were investigated. For the undoped β-Ga2O3, the transmittance is improved after annealing in oxygen or nitrogen atmosphere. After the introduction of Al element, the absorption cutoff appears slightly blue shift, and the band gap increases. For the undoped as-grown β-Ga2O3 single crystals, the decay time consists of a fast component (τ1) of the order of nanoseconds, and two slow components (τ2, τ3) of tens to hundreds of nanoseconds. The contribution of the fast decay time component in the decay times is 2.78%. While for Al-doped β-Ga2O3, the faster (τ1) time is 2.33 ns for the as-grown one, and the contribution is 68.02%. However, the pulse height spectrum shows that the introduction of 2.5 mol % Al will reduce the light yield of the β-Ga2O3 crystal.